Systematic review and meta-analysis of hemodynamic-directed feedback during cardiopulmonary resuscitation in cardiac arrest. (April 2016) - Chopra, A.S.; Wong, N.; Ziegler, C.P.; Morrison, L.J.
Abstract: Background/objective: Physiologic monitoring of resuscitative efforts during cardiac arrest is gaining in importance, as it provides a real-time window into the cellular physiology of patients. The aim of this review is to assess the quality of evidence surrounding the use of physiologic monitoring to guide cardiopulmonary resuscitation (CPR), and to examine whether the evidence demonstrates an improvement in patient outcome when comparing hemodynamic-directed CPR versus standard CPR. Methods: Studies were obtained through a search of the PubMed, Embase and Cochrane databases. Peer-reviewed randomized trials, case–control studies, systematic reviews, and cohort studies that titrated CPR to physiologic measures, compared results to standard CPR, and examined patient outcome were included. Results: Six studies met inclusion criteria, with all studies conducted in animal populations. Four studies examined the effects of hemodynamic-directed CPR on survival, with 35/37 (94.6%) animals surviving in the hemodynamic-directed CPR groups and 12/35 (34.3%) surviving in the control groups ( p < 0.001). Two studies examined the effects of hemodynamic-directed CPR on ROSC, with 22/30 (73.3%) achieving ROSC in the hemodynamic-directed CPR group and 19/30 (63.3%) achieving ROSC in the control group ( p = 0.344). Discussion/conclusion: These results suggest a trend in survival from hemodynamic-directed CPR over standard CPR, however the small sample size and lack of human data make these results of limited value. Future human studies examining hemodynamic-directed CPR versus current CPR standards are needed to enhance our understanding of how to effectively use physiologic measures to improve resuscitation efforts and ultimately incorporate concrete targets into international resuscitation guidelines.